2012
DOI: 10.5539/gjhs.v5n1p125
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and pattern of refractive errors among primary school children in Al Hassa , Saudi Arabia.

Abstract: Some 12.8 million in the age group 5–15 years are visually impaired from uncorrected or inadequately corrected refractive errors. In Saudi Arabia, the size of this public health problem is not well defined especially among primary schoolchildren. The purpose of this cross-sectional study was to assess the prevalence and pattern of refractive errors among primary school children in Al Hassa, Saudi Arabia. A total of 2246 Saudi primary school children aged 6 to 14 years of both genders were selected using multis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
107
7
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(133 citation statements)
references
References 27 publications
15
107
7
4
Order By: Relevance
“…Those who failed to obtain follow-up claimed that they had not been informed of their child's screening failure. Al Wadaani et al (2013) in contrast found that although the reported better access into eye care services in Al-Hassa, KSA, the prevalence of visual impairment from uncorrected refractive errors in some regions appears to be higher in urban areas than rural areas. Screening can enable important health problems to be identified earlier, offering effective interventions, but it is futile if follow-up or treatment is unavailable (Mathers, Keyes, & Wright, 2010).…”
Section: Importance Of Vision Screening For School Studentsmentioning
confidence: 85%
See 2 more Smart Citations
“…Those who failed to obtain follow-up claimed that they had not been informed of their child's screening failure. Al Wadaani et al (2013) in contrast found that although the reported better access into eye care services in Al-Hassa, KSA, the prevalence of visual impairment from uncorrected refractive errors in some regions appears to be higher in urban areas than rural areas. Screening can enable important health problems to be identified earlier, offering effective interventions, but it is futile if follow-up or treatment is unavailable (Mathers, Keyes, & Wright, 2010).…”
Section: Importance Of Vision Screening For School Studentsmentioning
confidence: 85%
“…Powell, Wedner, and Richardson (2005) reported that in normal visual development, changes in refractive error occur in the first few years of life. Undoubtedly, vision screening of preschool age and school children is a fundamental priority in detecting visual disorders, and preventing or correcting them at the appropriate time (Al Wadaani, Amin, Ali, & Khan, 2013;Bardisi & Bin Sadiq, 2002).…”
Section: Importance Of Vision Screening For School Studentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study from KSA, has examined 2246 Saudi primary school children aged 6 to 14 years of both genders. The study found that myopia was the most frequently met refractive error among both genders (65.7% of the total errors encountered) [4]. Another cross-sectional survey conducted in KSA included 21 primary schools with of 5176 children (mean age 9.5±1.8 years), the inclusive prevalence of RE was 18.6%, and astigmatism and myopia were the most common refractive error [3].…”
Section: Discussionmentioning
confidence: 99%
“…In the kingdom of Saudi Arabia (KSA), the prevalence of refractive error among children was up to 18.5% [3]. In study from Saudi Arabia investigated 2246 Saudi primary school children aged 6 to 14 years, Myopia was the most commonly encountered refractive error among both genders (65.7% of the total errors encountered [4].…”
Section: Introductionmentioning
confidence: 99%